Financial Performance Assessment of PT Idea Indonesia Akademi Tbk: A Ratio-Based Analysis in the E521 Sector - Muh Imdaadun Ni’am; M. Thoha Ainun Najib (MASALIQ, 2025)
This study is driven by the growing trend of educational institutions becoming publicly listed in Indonesia, highlighting the urgent need for a deeper understanding of financial health within this evolving sector. Focusing on PT Idea Indonesia Akademi Tbk, a pioneering public company in Indonesia’s education industry, this research analyzes its financial performance using a comprehensive financial ratio approach. Drawing on audited financial statements from fiscal years 2023 and 2024, the study examines four core categories of financial ratios: liquidity, solvency, activity, and profitability. Employing a qualitative descriptive-comparative methodology, the research aims to provide insights into the company’s financial dynamics during its post-IPO period. The findings show marked improvements in liquidity and capital structure, as reflected in higher current and quick ratios, an increased equity-to-asset ratio, and reduced debt levels. Conversely, profitability metrics, including Net Profit Margin, Return on Assets, and Return on Equity declined, indicating challenges in cost efficiency and revenue optimization. While inventory turnover improved substantially, a drop in receivable turnover suggests weaknesses in credit management. These mixed outcomes point to a strategic prioritization of financial stability, albeit at the expense of operational profitability. The study contributes to the limited literature on financial performance in the education sector, offering practical implications for investors, corporate management, and policymakers seeking to strengthen financial decision-making within publicly listed educational institutions in emerging markets.